2012
DOI: 10.4149/neo_2012_066
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and histomorphological analysis of rat mammary tumors after simvastatin treatment

Abstract: The results of experimental studies have indicated the pleiotropic effects of statins in organism, e.g. the influence on cell cycle, apoptosis or angiogenesis. In this study, the effects of simvastatin on selected parameters of apoptosis and proliferation in chemocarcinogen-induced mammary tumorigenesis in female rats were determined. Simvastatin was administered dietary at a dose of 18 mg/kg and highly effective dose of 180 mg/kg the entire experiment (18 weeks). At autopsy mammary tumors were removed and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 27 publications
0
10
0
1
Order By: Relevance
“…In our previous study a decrease in Ki67 protein expression by 27% in simvastatin‐treated rat mammary tumour cells was found (Kubatka et al . ). However, the tumour cell expression of Ki67 was not changed after fluvastatin administration in the same model (Kubatka et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…In our previous study a decrease in Ki67 protein expression by 27% in simvastatin‐treated rat mammary tumour cells was found (Kubatka et al . ). However, the tumour cell expression of Ki67 was not changed after fluvastatin administration in the same model (Kubatka et al .…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, significant anti‐tumour effects of dietary administered lipophilic statins (atorvastatin, simvastatin and fluvastatin) in the chemoprevention of rat mammary carcinogenesis in our previous studies were observed (Kubatka et al . , , ). In our recent experiment, hydrophilic rosuvastatin (250 mg/kg) has shown lower non‐significant anti‐neoplastic activity than lipophilic statins in this model of experimental breast cancer (Kubatka et al .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ezek a fehérjék a Ras/Raf/MEK/ ERK jelátviteli kaszkádra hatnak, amely a sejtosztódást serkenti [5]. Simvastatinnal kezelt patkányokban a Bcl-2/Bax protein arány proapoptotikus irányba billen, és ez a magas gradusú emlőcarcinoma-sejteket alacsony gradusúvá alakítja [6]. A lovastatin egerekben csökkentette a dohányzás indukálta tüdőadenomák többgócúságát, de ezek méretére és előfordulására nem volt befolyással [7].…”
Section: A Statinok Tumorképződésre Gyakorolt Hatásai áLlatkísérletekbenunclassified